2019
DOI: 10.3390/ijms20235940
|View full text |Cite
|
Sign up to set email alerts
|

Species Identification of Oaks (Quercus L., Fagaceae) from Gene to Genome

Abstract: Species identification of oaks (Quercus) is always a challenge because many species exhibit variable phenotypes that overlap with other species. Oaks are notorious for interspecific hybridization and introgression, and complex speciation patterns involving incomplete lineage sorting. Therefore, accurately identifying Quercus species barcodes has been unsuccessful. In this study, we used chloroplast genome sequence data to identify molecular markers for oak species identification. Using next generation sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 53 publications
5
46
1
Order By: Relevance
“…We identified three variable regions (ccsA-trnL, ΨndhE-ΨndhG-rps15, and ycf1) by comparing the Santalum chloroplast genomes. The ycf1 gene has been identified to be highly variable in several lineages, such as Dalbergia [78], Diospyros [62], and Quercus [79]. Studies have shown that ycf1 is phylogenetically useful [80] and is associated with a high success rate for DNA barcoding [81].…”
Section: Santalum Chloroplast Genome Evolution and Variationmentioning
confidence: 99%
“…We identified three variable regions (ccsA-trnL, ΨndhE-ΨndhG-rps15, and ycf1) by comparing the Santalum chloroplast genomes. The ycf1 gene has been identified to be highly variable in several lineages, such as Dalbergia [78], Diospyros [62], and Quercus [79]. Studies have shown that ycf1 is phylogenetically useful [80] and is associated with a high success rate for DNA barcoding [81].…”
Section: Santalum Chloroplast Genome Evolution and Variationmentioning
confidence: 99%
“…In previous studies, several unique characteristics of the plastome have been widely reported, such as its monophyletic inheritance [12], conserved coding region sequences [13] and genome structure [14,15]. These reliable resources provide rich information for the study of evolution, DNA barcoding, taxonomy and phylogeny [16][17][18]. Although the plastid genome is highly conserved, some interesting structural variations have been observed in some taxa, such as the rare expansion of IR regions in Strobilanthes [15], the insertion of mitochondrial DNA in the plastome of Anacardium [19], and the complete or partial loss of IR regions in some legumes [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…We identi ed three variable regions (ccsA-trnL, ΨndhE-ΨndhG-rps15, and ycf1) compared with the Santalum chloroplast genome. The ycf1 gene has been identi ed in several lineages, such as Dalbergia [39], Diospyros [22], and Quercus [40]. Studies have shown that ycf1 is phylogenetically useful [41] and is associated with a high success rate for DNA barcoding [42].…”
Section: Santalum Chloroplast Genome Evolution and Variationmentioning
confidence: 99%